Composite colored sand coating and preparation method thereof
Through the preparation of modifiers and modified polypropylene fibers, combined with the use of antibacterial monomers, the problem of insufficient antibacterial and cracking performance of the existing color sand coatings, and realized the multi -functional improvement of composite color sand coatings Essence
Patent Information
- Application Number
- CN202411087673.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-08-09
AI Technical Summary
The existing colored sand coatings lack good antibacterial and crack resistance, which limits their application scope.
Through the preparation of modifiers and modified polypropylene fiber, antibacterial monomers and sodium -based Mongolia are removed from soil and peroxybenzohide and polypropylene fiber reactions, forming a long chain monopoly ammonium salt and benzene ring structure Antibacterial monomer molecules are modified and deepened and modified polypropylene fibers, and they are added to colored sand coatings.
It significantly enhances the antibacterial properties and antibacterial durability of composite color sand coatings. At the same time, it improves the crack resistance and adhesion strength of the coating, and enhances its water resistance, acid resistance and aging resistance.
Smart Images

Figure BDA0004985621630000031 
Figure BDA0004985621630000051 
Figure BDA0004985621630000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a composite colored sand coating and a preparation method thereof. Background Art
[0002] Real stone paint is a kind of paint with decorative effect similar to marble and granite. It has the advantages of natural and real natural color, fire resistance, waterproof, acid and alkali resistance, pollution resistance, non-toxicity, odorlessness, strong adhesion, and never fading. It is widely used in the decoration of various buildings. It can effectively prevent the erosion of buildings by harsh external environment and help to extend the life of buildings. However, real stone paint is mainly made of natural stone powder of various colors from nature as raw materials. In order to ease the tension of non-renewable natural resources, people are gradually using simulated stone paint (colored sand paint) instead of real stone paint. At the same time, higher and higher requirements are also put forward for the performance of colored sand paint. In addition to meeting the basic performance requirements of the paint, it is sometimes also required to have multifunctional functions such as noise reduction, anti-fouling, mildew resistance and antibacterial.
[0003] Chinese patent application with application number 202110111605.8 discloses a colored sand paint and its preparation method and application, comprising the following components in parts by weight: 840-1200 parts of colored hollow glass microspheres, 400-680 parts of polymer emulsion, 7-10 parts of film-forming aid, 7-10 parts of antifreeze and 5-10 parts of cellulose. The prepared colored sand paint has the characteristics of light weight, good aging resistance and good thermal insulation effect. At the same time, its color is not limited by the color of natural colored sand, and it is suitable for use as a building paint. However, the colored sand paint does not have a functional effect, which limits its application; Chinese patent application with application number 202410312690.8 discloses a lightweight real stone paint for interior walls and its preparation method, comprising the following components in mass percentage The components of the invention include: emulsion 15%-20%, modified titanium dioxide 0.5%-1.5%, filler 45%-60%, thickener 0.6%-1%, defoamer 0.6%-0.8%, wetting agent 0.3%-0.5%, dispersant 0.5-0.7%, film-forming aid 2%-2.2%, antifreeze 1%-1.2%, mildew inhibitor 0.1%-0.2%, pH regulator 0.1%-0.15% and balance water. The modified titanium dioxide and modified perlite are mixed to make the real stone paint have excellent antibacterial effect. The added mildew inhibitor prevents the interior wall lightweight real stone paint from peeling and mildewing, thereby ensuring the antibacterial and anti-fouling effect of the interior wall lightweight real stone paint. However, the antibacterial and crack resistance of the real stone paint are insufficient, and there is still a lot of room for improvement.
[0004] Therefore, it is necessary to develop a multifunctional colored sand coating with good antibacterial and anti-cracking properties to meet market demand. Summary of the invention
[0005] The purpose of the present invention is to provide a composite colored sand coating and a preparation method thereof in view of the deficiencies in the prior art. The prepared composite colored sand coating has a short drying time, good crack resistance, high bonding strength, good water resistance, acid and alkali resistance and aging resistance, and especially excellent antibacterial property and antibacterial durability.
[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:
[0007] A composite colored sand coating, the coating comprising the following components in parts by weight: 120-130 parts of colored sand; 60-70 parts of silicone-acrylic emulsion; 8-10 parts of silica sol; 6-10 parts of modified montmorillonite; 5-8 parts of modified polypropylene fiber; 3-5 parts of film-forming aid; 0.3-0.5 parts of thickener; 0.2-0.4 parts of defoamer; 10-15 parts of deionized water;
[0008] In the technical solution of the present invention, the film-forming aid is one or a mixture of ethylene glycol phenyl ether, dodecyl alcohol ester, and ethylene glycol monobutyl ether, and the preferred film-forming aid is dodecyl alcohol ester.
[0009] In the technical solution of the present invention, the thickener is one or a mixture of hydroxyethyl cellulose, hydroxypropyl methyl cellulose and hydroxypropyl cellulose, and the preferred thickener is hydroxypropyl cellulose.
[0010] In the technical solution of the present invention, the defoaming agent is a silicone defoaming agent.
[0011] In the technical solution of the present invention, the preparation method of the modified montmorillonite is as follows: add water and sodium montmorillonite to a reaction container, disperse them evenly, add antibacterial monomer, heat to 50-60°C, stir and react for 5-6h, cool after the reaction is completed, filter, and repeatedly wash the product with water, dry and grind to obtain modified montmorillonite;
[0012] Furthermore, in the preparation method of modified montmorillonite, the mass ratio of sodium-montmorillonite, antibacterial monomer and water is 1:0.2-0.3:20-25, preferably the mass ratio of sodium-montmorillonite, antibacterial monomer and water is 1:0.3:25.
[0013] In the technical scheme of the present invention, the preparation method of the modified polypropylene fiber is as follows: xylene, antibacterial monomer and benzoyl peroxide are added to a reaction container, stirred evenly, immersed in polypropylene fiber, heated to 100-110°C, reacted for 3-4 hours, after the reaction is completed, cooled, filtered, and washed with xylene and acetone in turn, and dried to obtain modified polypropylene fiber.
[0014] Furthermore, in the preparation method of modified polypropylene fiber, the mass ratio of polypropylene fiber, antibacterial monomer and benzoyl peroxide is 1:0.2-0.3:0.01-0.02, and preferably the mass ratio of polypropylene fiber, antibacterial monomer and benzoyl peroxide is 1:0.3:0.02.
[0015] In the technical solution of the present invention, the structural formula of the antibacterial monomers used in the preparation methods of modified montmorillonite and modified polypropylene fibers are:
[0016]
[0017] Furthermore, the preparation method of the antibacterial monomer is: firstly react p-chlorobenzyl alcohol and dodecyl dimethyl tertiary amine at 80° C. for 8-10 hours to obtain an intermediate 1 having the structural formula:
[0018] The reaction solvent used is ethanol; intermediate 1 and 4-chlorobutyric acid are then reacted at 110° C. for 4-6 hours under the catalysis of p-toluenesulfonic acid to obtain intermediate 2, the structural formula of which is:
[0019] The reaction solvent used is toluene; finally, the intermediate 2 and dimethylaminoethyl methacrylate are reacted at 70-80° C. for 6-8 hours to obtain an antibacterial monomer, and the reaction solvent used is acetonitrile.
[0020] Furthermore, in the preparation method of the antibacterial monomer, the molar ratio of p-chlorobenzyl alcohol and dodecyl dimethyl tertiary amine is 1:1-1.1; the molar ratio of the intermediate 1, 4-chlorobutyric acid and p-toluenesulfonic acid is 1:1-1.1:0.03-0.05; the molar ratio of dimethylaminoethyl methacrylate and intermediate 2 is 1:1-1.1.
[0021] The present invention also provides a method for preparing a composite colored sand coating, comprising the following steps: firstly mixing silicone acrylic emulsion, silica sol, modified montmorillonite, modified polypropylene fiber, film-forming aid, thickener, defoamer and deionized water according to a weight ratio and stirring for 20-30 minutes, adding colored sand, and continuing stirring for 30-40 minutes to obtain the composite colored sand coating.
[0022] The present invention has the following beneficial effects:
[0023] In order to obtain a multifunctional colored sand coating with good antibacterial and crack resistance, the components of the colored sand coating are modified. On the one hand, sodium montmorillonite is used as a raw material, and the property of exchanging cations is utilized to react with an antibacterial monomer containing multiple quaternary ammonium salts to obtain modified montmorillonite. On the other hand, polypropylene fiber is used as a raw material, and under the action of benzoyl peroxide, the antibacterial monomer is reacted to obtain modified polypropylene fiber. The modified montmorillonite and modified polypropylene fiber prepared by the present invention both contain a long-chain quaternary ammonium salt with a dispersing effect, multiple quaternary ammonium salts with antibacterial effects, and antibacterial monomer molecules with a benzene ring structure. The long-chain quaternary ammonium salt structure with a dispersing effect can not only make the modified montmorillonite have better suspension and dispersion stability, but also improve the suspension stability of the coating, and contribute to It can improve the comprehensive performance of the coating and prevent the modified polypropylene fiber from agglomerating, so that it can be evenly dispersed in the coating. In addition, the benzene ring structure can also improve the linear structure of the individual polypropylene fiber, giving it a certain rigidity, thereby improving the crack resistance and bonding strength of the coating; the quaternary ammonium salt structure with multiple antibacterial effects can significantly enhance the antibacterial properties of modified montmorillonite and modified polypropylene fiber, especially the modified montmorillonite also has a strong adsorption effect. Bacteria can first be adsorbed to the surface of the modified montmorillonite, and then slowly deformed and died. At the same time, the antibacterial monomers of multiple quaternary ammonium salts can also be continuously desorbed from the modified montmorillonite, and their antibacterial effects can be exerted for a long time. The modified montmorillonite and modified polypropylene fiber in the components can synergistically exert multiple antibacterial effects, thereby significantly improving the antibacterial performance and antibacterial durability of the coating.
[0024] The composite colored sand coating provided by the present invention uses colored sand and silicone-acrylic emulsion as main components, and adds components such as silica sol, modified montmorillonite, modified polypropylene fiber, film-forming aid, thickener, etc. By reasonably controlling the weight ratio of each component, the composite colored sand coating with short drying time, good crack resistance, high bonding strength, good water resistance, acid and alkali resistance and aging resistance, especially excellent antibacterial property and antibacterial durability is obtained. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments; the technical features designed in different implementation modes of the present invention described below can be combined with each other as long as they do not conflict with each other; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] In the technical scheme of the present invention, the chemical reagents used are all commonly available on the market, among which the viscosity of the silicone-acrylic emulsion is 700mPa·s, the pH value is 8, and the solid content is 52wt%; the SiO2 content in the silica sol is 20-30%, and the average particle size is 20-30nm; the diameter of the polypropylene fiber is 10-20μm and the length is 3mm; ethylene glycol phenyl ether CAS No. 122-99-6; dodecanol ester CAS No. 25265-77-4; ethylene glycol monobutyl ether CAS No. 111-76-2; hydroxyethyl cellulose CAS No. 9004-62-0; hydroxypropyl methylcellulose CAS No. 9004-65-3; hydroxypropyl cellulose CAS No. 9004-64-2; dimethyl silicone oil CAS No. 9006-65-9.
[0027] In the technical solution of the present invention, the preparation method of the antibacterial monomer is:
[0028]
[0029] 15.0 g of p-chlorobenzyl alcohol and 22.5 g of dodecyl dimethyl tertiary amine were added to 500 mL of ethanol, stirred evenly, and reacted at 80°C for 10 h. After the reaction was completed, the mixture was cooled, the ethanol was removed, and the mixture was extracted with water and dichloromethane. The aqueous phase was concentrated under reduced pressure to obtain 32.8 g of intermediate 1; the molar ratio of p-chlorobenzyl alcohol to dodecyl dimethyl tertiary amine was 1:1; intermediate 1: ESI (m / z): 356.9 [M+H] + , 1 H-NMR (600MHz, DMSO-d6, δppm): 7.28 (d, J=8.6Hz, 2H), 7.03 (d, J=8.6Hz, 2H), 5.27 (s, 1H), 4.61 (s, 2H), 3.72 (s, 6H), 3.22-3.25 (m, 2H), 1.71-1.74 (m, 2H), 1.26-1.30 (m, 18H), 0.88 (t, J=6.5Hz, 3H).
[0030] Then, 18.0 g of intermediate 1, 6.2 g of 4-chlorobutyric acid and 0.3 g of p-toluenesulfonic acid were added to 250 mL of toluene, stirred evenly, and reacted at 110° C. for 6 h. After the reaction was completed, the mixture was cooled, toluene was removed, and the mixture was extracted with water and dichloromethane. The aqueous phase was concentrated under reduced pressure to obtain 20.4 g of intermediate 2; the molar ratio of intermediate 1, 4-chlorobutyric acid and p-toluenesulfonic acid was 1:1:0.03; intermediate 2: ESI (m / z): 461.5 [M+H] + , 1H-NMR (600MHz, DMSO-d6, δppm): 7.28 (d, J=8.6Hz, 2H), 7.04 (d, J=8.6Hz, 2H), 5.20 (s, 2H), 3.72 (s, 6H), 3.65-3 .68 (m, 2H), 3.23-3.25 (m, 2H), 2.32-2.36 (m, 2H), 1.75-1.80 (m, 4H), 1.26-1.30 (m, 18H), 0.88 (t, J=6.5Hz, 3H).
[0031] Finally, 5.1 g of dimethylaminoethyl methacrylate and 15.0 g of intermediate 2 were added to 200 mL of acetonitrile, stirred evenly, and reacted at 80°C for 8 h. After the reaction was completed, the mixture was cooled, acetonitrile was removed, and the mixture was extracted with water and dichloromethane. The aqueous phase was concentrated under reduced pressure to obtain 16.5 g of antibacterial monomer; the molar ratio of dimethylaminoethyl methacrylate to intermediate 2 was 1:1; antibacterial monomer: ESI (m / z): 618.7 [M+H] + , 1 H-NMR (600MHz, DMSO-d6, δppm): 7.29 (d, J=8.6Hz, 2H), 7.03 (d, J=8.6Hz, 2H) , 6.42-6.46(m, 2H), 5.22(s, 2H), 4.59-4.62(m, 2H), 3.72(s, 6H), 3.52-3.55 (m, 2H), 3.30 (s, 6H), 3.23-3.25 (m, 4H), 2.32-2.35 (m, 2H), 2.21-2.24 (m, 2H ), 2.01 (s, 3H), 1.75-1.80 (m, 2H), 1.26-1.30 (m, 18H), 0.88 (t, J=6.5Hz, 3H).
[0032] Example 1
[0033] A composite colored sand paint comprises the following components by weight: 130 parts of colored sand; 65 parts of silicone-acrylic emulsion; 10 parts of silica sol; 8 parts of modified montmorillonite; 8 parts of modified polypropylene fiber; 5 parts of film-forming aid; 0.5 parts of thickener; 0.4 parts of defoamer; 15 parts of deionized water;
[0034] The film-forming aid is dodecyl alcohol ester; the thickener is hydroxypropyl cellulose; and the defoaming agent is dimethyl silicone oil, a silicone defoaming agent.
[0035] The preparation method of modified montmorillonite is as follows: add water and sodium montmorillonite into a reaction container, disperse them evenly, add antibacterial monomer, heat to 60°C, stir and react for 5 hours, and after the reaction is completed, cool, filter, and repeatedly wash the product with water, dry and grind to obtain modified montmorillonite; the mass ratio of sodium montmorillonite, antibacterial monomer and water is 1:0.3:25.
[0036] Preparation method of modified polypropylene fiber: add xylene, antibacterial monomer and benzoyl peroxide into a reaction container, stir evenly, immerse polypropylene fiber, heat to 110°C, react for 3 hours, after the reaction is completed, cool, filter, and wash with xylene and acetone in turn, and obtain modified polypropylene fiber after drying; the mass ratio of polypropylene fiber, antibacterial monomer, and benzoyl peroxide is 1:0.3:0.02.
[0037] A preparation method of a composite colored sand coating comprises the following steps: firstly, according to a weight ratio, mixing silicone acrylic emulsion, silica sol, modified montmorillonite, modified polypropylene fiber, film-forming aid, thickener, defoamer and deionized water for 30 minutes, adding colored sand, and continuing to stir for 40 minutes to obtain the composite colored sand coating.
[0038] Example 2
[0039] A composite colored sand paint comprises the following components by weight: 125 parts of colored sand; 70 parts of silicone-acrylic emulsion; 8 parts of silica sol; 10 parts of modified montmorillonite; 7 parts of modified polypropylene fiber; 4 parts of film-forming aid; 0.3 parts of thickener; 0.2 parts of defoamer; 13 parts of deionized water;
[0040] The film-forming aid is ethylene glycol phenyl ether; the thickener is hydroxyethyl cellulose; and the defoaming agent is dimethyl silicone oil, a silicone defoaming agent.
[0041] The preparation method of modified montmorillonite is as follows: add water and sodium montmorillonite into a reaction container, disperse them evenly, add antibacterial monomer, heat to 50°C, stir and react for 6 hours, and after the reaction is completed, cool, filter, and repeatedly wash the product with water, dry and grind to obtain modified montmorillonite; the mass ratio of sodium montmorillonite, antibacterial monomer and water is 1:0.25:20.
[0042] Preparation method of modified polypropylene fiber: add xylene, antibacterial monomer and benzoyl peroxide into a reaction container, stir evenly, immerse polypropylene fiber, heat to 100°C, react for 4 hours, after the reaction is completed, cool, filter, and wash with xylene and acetone in turn, and obtain modified polypropylene fiber after drying; the mass ratio of polypropylene fiber, antibacterial monomer, and benzoyl peroxide is 1:0.2:0.01.
[0043] The preparation method of a composite colored sand coating is the same as that of Example 1.
[0044] Example 3
[0045] A composite colored sand paint comprises the following components by weight: 120 parts of colored sand; 60 parts of silicone-acrylic emulsion; 9 parts of silica sol; 6 parts of modified montmorillonite; 5 parts of modified polypropylene fiber; 3 parts of film-forming aid; 0.4 parts of thickener; 0.3 parts of defoamer; 10 parts of deionized water;
[0046] The film-forming aid is ethylene glycol monobutyl ether; the thickener is hydroxypropyl methylcellulose; and the defoaming agent is dimethyl silicone oil, a silicone defoaming agent.
[0047] The preparation method of modified montmorillonite is as follows: add water and sodium montmorillonite into a reaction container, disperse them evenly, add antibacterial monomer, heat to 55°C, stir and react for 5.5 hours, and after the reaction is completed, cool, filter, and repeatedly wash the product with water, dry and grind to obtain modified montmorillonite; the mass ratio of sodium montmorillonite, antibacterial monomer and water is 1:0.2:22.
[0048] Preparation method of modified polypropylene fiber: add xylene, antibacterial monomer and benzoyl peroxide into a reaction container, stir evenly, immerse polypropylene fiber, heat to 105°C, react for 3.5 hours, after the reaction is completed, cool, filter, and wash with xylene and acetone in turn, and obtain modified polypropylene fiber after drying; the mass ratio of polypropylene fiber, antibacterial monomer, and benzoyl peroxide is 1:0.25:0.015.
[0049] The preparation method of a composite colored sand coating is the same as that of Example 1.
[0050] Example 4
[0051] A composite colored sand paint comprises the following components by weight: 130 parts of colored sand; 70 parts of silicone-acrylic emulsion; 9 parts of silica sol; 7 parts of modified montmorillonite; 6 parts of modified polypropylene fiber; 3 parts of film-forming aid; 0.3 parts of thickener; 0.4 parts of defoamer; 12 parts of deionized water;
[0052] The film-forming aid is ethylene glycol phenyl ether; the thickener is hydroxypropyl cellulose; and the defoaming agent is dimethyl silicone oil, a silicone defoaming agent.
[0053] The preparation method of modified montmorillonite is the same as that in Example 1.
[0054] The preparation method of modified polypropylene fiber is the same as that in Example 2.
[0055] The preparation method of a composite colored sand coating is the same as that of Example 1.
[0056] Comparative Example 1
[0057] Compared with Example 1, this comparative example does not perform modification of the sodium-montmorillonite.
[0058] A composite colored sand paint comprises the following components by weight: 130 parts of colored sand; 65 parts of silicone-acrylic emulsion; 10 parts of silica sol; 8 parts of sodium montmorillonite; 8 parts of modified polypropylene fiber; 5 parts of film-forming aid; 0.5 parts of thickener; 0.4 parts of defoamer; 15 parts of deionized water;
[0059] The film-forming aid is dodecyl alcohol ester; the thickener is hydroxypropyl cellulose; and the defoaming agent is dimethyl silicone oil, a silicone defoaming agent.
[0060] The preparation methods of modified polypropylene fiber and composite colored sand coating are the same as those in Example 1.
[0061] Comparative Example 2
[0062] Compared with Example 1, this comparative example does not modify the polypropylene fiber.
[0063] A composite colored sand paint comprises the following components by weight: 130 parts of colored sand; 65 parts of silicone-acrylic emulsion; 10 parts of silica sol; 8 parts of modified montmorillonite; 8 parts of polypropylene fiber; 5 parts of film-forming aid; 0.5 parts of thickener; 0.4 parts of defoamer; 15 parts of deionized water;
[0064] The film-forming aid is dodecyl alcohol ester; the thickener is hydroxypropyl cellulose; and the defoaming agent is dimethyl silicone oil, a silicone defoaming agent.
[0065] The preparation methods of modified montmorillonite and composite colored sand coating are the same as those in Example 1.
[0066] Comparative Example 3
[0067] Compared with Example 1, this comparative example does not perform modification on the sodium-montmorillonite and polypropylene fiber.
[0068] A composite colored sand paint comprises the following components by weight: 130 parts of colored sand; 65 parts of silicone-acrylic emulsion; 10 parts of silica sol; 8 parts of sodium montmorillonite; 8 parts of polypropylene fiber; 5 parts of film-forming aid; 0.5 parts of thickener; 0.4 parts of defoamer; 15 parts of deionized water;
[0069] The film-forming aid is dodecyl alcohol ester; the thickener is hydroxypropyl cellulose; and the defoaming agent is dimethyl silicone oil, a silicone defoaming agent.
[0070] The preparation method of a composite colored sand coating is the same as that of Example 1.
[0071] The composite colored sand coatings prepared in Examples 1-4 and Comparative Examples 1-3 were subjected to performance tests, wherein the drying time was based on the standard GB / T 1728-1979; the initial drying crack resistance, bonding strength, water resistance, acid and alkali resistance were based on the standard JG / T24-2018; the aging resistance was based on the standard GB / T 1865-2009 test time of 600h; the results are shown in Table 1.
[0072] Table 1 Performance test results of composite colored sand coating
[0073]
[0074] The antibacterial performance of the composite colored sand coatings prepared in Examples 1-4 and Comparative Examples 1-3 was tested. Referring to the standard GB / T21866-2008, the antibacterial rate of the samples after 24h and 48h of incubation was tested, and a 30W ultraviolet lamp with a wavelength of 253.7nm in accordance with GB19258 was used. The samples were irradiated at a distance of 0.8-1.0m from the ultraviolet lamp for 100h and the antibacterial durability was tested. The results are shown in Table 2.
[0075] Table 2 Antibacterial performance test results of composite colored sand coating
[0076] sample 24h antibacterial rate (%) 48h antibacterial rate (%) Antibacterial durability (%) Example 1 99.9 99.9 98.5 Example 2 99.8 99.7 97.6 Example 3 99.6 99.6 97.1 Example 4 99.9 99.8 98.2 Comparative Example 1 84.6 78.5 66.9 Comparative Example 2 83.8 75.9 64.8 Comparative Example 3 69.3 58.8 42.5
[0077] It can be seen from the results in Table 1 that the composite colored sand coatings prepared in Examples 1-4 of the present invention have short drying time, good initial drying crack resistance, high bonding strength, good water resistance, acid and alkali resistance and aging resistance, indicating that the composite colored sand coating has excellent comprehensive performance; compared with Comparative Examples 1-3, modified montmorillonite and modified polypropylene fiber are added to the components of the composite colored sand coating in Example 1 of the present invention, both of which contain antibacterial monomer molecules with long-chain quaternary ammonium salts and benzene ring structures with dispersing effects. For modified montmorillonite, it can have better suspension and dispersion stability, thereby improving the suspension stability of the coating, which is helpful to improve the comprehensive performance of the coating; for modified polypropylene fiber, it can prevent its agglomeration so that it can be evenly dispersed in the coating, and the benzene ring structure in the modified polypropylene fiber can also improve the linear structure of the single polypropylene fiber, giving it a certain rigidity, thereby improving the crack resistance and bonding strength of the coating.
[0078] It can be seen from the results in Table 2 that the composite colored sand coatings prepared in Examples 1-4 of the present invention have higher 24h and 48h antibacterial rates and antibacterial durability, indicating that the composite colored sand coatings have excellent antibacterial properties; compared with Comparative Examples 1-3, modified montmorillonite and modified polypropylene fiber are added to the components of the composite colored sand coating in Example 1 of the present invention, both of which contain antibacterial monomer molecules with quaternary ammonium salt structures having multiple antibacterial effects, which can significantly enhance the antibacterial properties of the modified montmorillonite and the modified polypropylene fiber, especially the modified montmorillonite also has a strong adsorption effect, and bacteria can first be adsorbed to the surface of the modified montmorillonite, and then slowly deformed and died, while the antibacterial monomers of multiple quaternary ammonium salts can also be continuously desorbed from the modified montmorillonite, and their antibacterial effects are exerted for a long time, and the modified montmorillonite and modified polypropylene fiber synergistically exert multiple antibacterial effects, thereby significantly improving the antibacterial property and antibacterial durability of the coating.
[0079] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0080] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A composite colored sand coating, characterized in that: The coating comprises the following components by weight: 120-130 parts of colored sand; 60-70 parts of silicone-acrylic emulsion; 8-10 parts of silica sol; 6-10 parts of modified montmorillonite; 5-8 parts of modified polypropylene fiber; 3-5 parts of film-forming aid; 0.3-0.5 parts of thickener; 0.2-0.4 parts of defoamer; 10-15 parts of deionized water; The preparation method of the modified montmorillonite is as follows: water and sodium montmorillonite are added to a reaction container, dispersed evenly, antibacterial monomer is added, the temperature is raised to 50-60° C., stirred for reaction for 5-6 hours, after the reaction is completed, cooled, filtered, and the product is repeatedly washed with water, dried, and ground to obtain modified montmorillonite; the structural formula of the antibacterial monomer is: The preparation method of the modified polypropylene fiber comprises the following steps: adding xylene, antibacterial monomer and benzoyl peroxide into a reaction container, stirring evenly, immersing the polypropylene fiber, heating to 100-110° C., reacting for 3-4 hours, cooling after the reaction is completed, filtering, washing with xylene and acetone in turn, and drying to obtain the modified polypropylene fiber.
2. A composite colored sand coating according to claim 1, characterized in that: In the preparation method of modified polypropylene fiber, the mass ratio of the polypropylene fiber, the antibacterial monomer and benzoyl peroxide is 1:0.2-0.3:0.01-0.
02.
3. A composite colored sand coating according to claim 1, characterized in that: In the preparation method of modified montmorillonite, the mass ratio of sodium-based montmorillonite, antibacterial monomer and water is 1:0.2-0.3:20-25.
4. A composite colored sand coating according to claim 1, characterized in that: The preparation method of the antibacterial monomer is as follows: firstly, p-chlorobenzyl alcohol and dodecyl dimethyl tertiary amine are reacted at 80° C. for 8-10 hours to obtain intermediate 1; then, intermediate 1 and 4-chlorobutyric acid are reacted at 110° C. for 4-6 hours under the catalytic action of p-toluenesulfonic acid to obtain intermediate 2; finally, intermediate 2 and dimethylaminoethyl methacrylate are reacted at 70-80° C. for 6-8 hours to obtain the antibacterial monomer.
5. A composite colored sand coating according to claim 1, characterized in that: The film-forming aid is one or a mixture of ethylene glycol phenyl ether, dodecyl alcohol ester, and ethylene glycol monobutyl ether.
6. A composite colored sand coating according to claim 1, characterized in that: The thickener is one or a mixture of hydroxyethyl cellulose, hydroxypropyl methyl cellulose and hydroxypropyl cellulose.
7. A composite colored sand coating according to claim 1, characterized in that: The defoaming agent is a silicone defoaming agent.
8. A method for preparing the composite colored sand coating according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: firstly mixing silicone acrylic emulsion, silica sol, modified montmorillonite, modified polypropylene fiber, film-forming aid, thickener, defoamer and deionized water according to weight ratio for 20-30 minutes, adding colored sand, and continuing to stir for 30-40 minutes to obtain composite colored sand coating.
Citation Information
Patent Citations
Storage battery plate
CA111762A
Electric curling irons
CA122996A
Colored sand coating and preparation method and application thereof
CN112759985A
Light stone-like coating for interior wall and preparation method of light stone-like coating
CN118085660A
Preparation method of nanometer resin with high hygroscopy
CN101787101A